Method of quick decrement count with linear hardware increasing when orders are adding - Azarov, O. D.; Cherniak, O. I. (Visnyk of Vinnytsia Politechnical Institute, 2015)
The method and structural organization of quick decrement count in Fibonacci numerical system are described, which allow creating of counters with high speed and linear hardware increasing when orders are adding.